Problematic of massively multiplayer online game addiction in Malaysia - Muhaimin, M. (2019)
This study aimed to find causes of online game addiction among adolescents in Malaysia specifically focus on massively multiplayer online games (MMOG) in Malaysia. The relationship between causes and the addiction components will be investigated. This study used focus group discussion (FGD) as research methodology. Results showed that 3 main causes have been revealed which include; poor time management in which adolescents failed to manage their time wisely, social life in which they make more friends in virtual life compared to in real life and psychological and behavior which affect adolescentâs emotion and physical. Addiction components that had been discussed are linked to 3 main factors identified from previous study. The identified components that found influence gaming addiction among adolescents are; salience, mood modification, harm, loss of control and physical health are related to main causes of adolescents addicted to MMOG in Malaysia. Evidences that have been revealed by both medical experts and game experts had explored the highly engaging relationship between adolescent and MMOG addictive behavior which can be seen by observation through physical health. Â© Springer Nature Switzerland AG 2019.